Advances in the diagnosis of exosomal miRNAs in ischemic stroke - Yu P (Dove Medical Press, 2019)
Pei Yu,1 Wencheng Chen21Department of Clinical Laboratory, Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, Guangxi 533000, People’s Republic of China; 2Department of Clinical Laboratory, Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, Guangxi 533000, People’s Republic of ChinaCorrespondence: Wencheng ChenDepartment of Clinical Laboratory Affiliated Hospital of Youjiang Medical University for Nationalities, No.18, Zhongshan Street, Youjiang District, Baise, Guangxi 533000, People’s Republic of ChinaTel +86 0 776 284 6532Fax +86 0 776 283 5992Email chwch3268@sina.comAbstract: Early diagnosis, early treatment, and improved prognosis in patients with ischemic stroke are vital requirements. Current clinical practices for the diagnosis of stroke include computed tomography, magnetic resonance imaging, and other traditional imaging methods to quickly check the location, volume, etc, in the hospital; however, diagnosis of the underlying cause of infarction is not effective with these practices. Owing to the coexistence of various etiologies, accurate and timely diagnosis using routine hematology and biochemical tests remains a challenge. Exosomes are membrane vesicles, approximately 30–150 nm in diameter, which fuse with cell membrane and are released into the extracellular space. As one of the research hotspots in the field of medicine in recent years, exosomes can participate in immune response, antigen presentation, cell migration, tumor invasion, and so on. Owing to the important role played by the miRNAs contained in exosomes, the latter have shown great potential in the diagnosis and treatment of ischemic stroke. This article reviews the progress made regarding the exosomal miRNAs as ischemic stroke biomarkers.Keywords: exosome, transporter, prognosis, intercellular communication